A biopsychosocial model of body image, disordered eating, and breastfeeding among postpartum women. (1st July 2018) - Rodgers, Rachel F.; O'Flynn, Jennifer L.; Bourdeau, Althea; Zimmerman, Emily
Abstract: Background: The aim of the current study was to test a biopsychosocial model of body image, eating, and feeding attitudes among postpartum women. Specifically, the model predicted that desired weight-loss, depressive symptoms, and body surveillance would predict body dissatisfaction and appearance-related barriers to breastfeeding, which in turn would predict maternal disordered eating and breastfeeding self-efficacy. Methods: Data from 151 women, mean age = 32.77 (4.47) years, who provided complete data in response to an online survey were analyzed. Results: Path analysis revealed that after minor modifications, the biopsychosocial model was a good fit to the data. Desired weight-loss, depressive symptoms, and body surveillance were associated with higher levels of disordered eating and lower levels of breastfeeding self-efficacy directly, as well as indirectly through body dissatisfaction and appearance-related barriers to breastfeeding. Conclusion: Findings provide support for an integrated biopsychosocial model of body image concerns, and eating and feeding attitudes among postpartum women as well as highlighting the need for additional support around body image, eating, and breastfeeding following childbirth. Our study has clinical implications for healthcare providers working with new mothers and can be used to inform postpartum psychoeducation efforts addressing breastfeeding, weight loss expectations and body image concerns.